Two mammalian heat shock proteins, HSP90 and HSP100, are actin-binding proteins. - Koyasu, S (1986)
Two high molecular weight heat shock proteins, HSP90 (Mr, 90,000) and HSP100 (Mr, 100,000), were separately purified from extracts of cultured cells of a mouse lymphoma cell line, L5178Y. Both of the HSPs exist in homodimeric form under physiological conditions. Their physicochemical properties are quite similar to each other. Each of the purified HSPs was shown to coprecipitate with rabbit skeletal muscle actin under actin-polymerizing conditions. Both HSP90 and HSP100 increased the low-shear viscosity of filamentous actin solutions in a dose-dependent manner, which suggests that these HSPs cross-link actin filaments. Although some molecular properties and the effects described above on actin solution of HSP90 and HSP100 resemble those of alpha-actinin, the HSPs were distinguished from alpha-actinin by various means, including visualization of molecular shapes by electron microscopy with the aid of the low-angle rotary shadowing technique. Immunofluorescence staining by specific antisera against HSP90 revealed that HSP90 was localized in ruffling membranes in addition to the cytoplasmic space.